Penggunaan indikator peraturan kelayakan berasas pendapatan dan peluang kanak-kanak mendapat bantuan sosial awam - Ilias, Normila; Abu Bakar Ah, Siti Hajar; Zakaria, Abd Hadi (The Malaysian Journal of Social Administration, 2017)
Well-being of a child is closely related to the socio-economic status of his/her household. Economic deprivation of one’s household not only contributes to child poverty; but also have some bearing on the child’s likelihood to be considered as an eligible public social assistance recipient. A survey was carried out in 2007 to examine the ways in which socio-economic statuses of households impinged on a child’s opportunity to receive social assistance. A total of 230 children, who were listed in the application list of Child Benefits Scheme administered by the Social Welfare Department in Pasir Puteh District, Kelantan were involved in the study. The findings show that there is a significant relationship (p>.000) between the socio-economic characteristics and a child’s likelihood to be eligible for social assistance. The findings also indicate that eligibility rules which are based on income (means test) are pertinent in the selection of eligible public social assistance recipients.